Female Sexual Assualt: Prevalence of Positive Cases from a Tertiary Care Center of Province Khyber Pakhtunkhwa - Muhammad Bilal Khan, Khalid Saleem, Muhammad Arshad Hussain, Atta Ullah, Tariq Ali, Ijaz Aziz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the prevalence of recent/current positive cases in sexually assaulted female cases reported at a tertiary care center of the province Khyber Pakhtunkhwa. Methodology: The study was designed as cross-sectional observational in nature and was conducted at District Headquarter Hospital, Swabi on a sample of 93 victims. The study span was from Jan 2021 to Dec 2021, while sample was enrolled using non-probability convenience sampling. After following ethical consideration, a pre-designed performa was used to collect the data which included demographic and sexual assault related queries. SPSS v.25.0 was used as tool to analyze and interpret data; descriptive and advanced statistics were used where needed. Results: In a study sample of 93 patients, the mean age was recorded as 22.84+6.71 years with range of 4 to 41 years. In age group, age between 10-19 years was found to be most prone for assault 35 (37.63%), followed by 20-29 years 23 (25%). The study revealed that maximum of the victims were reported after 72 hours of the incident 52 (55.91%), followed by those reported in 48-72 hours 20 (21.51%). It was revealed that in 63 (67.74%) of the victims, assailant was known to her. Injuries to genital area showed that 80 (86.2%) of the victims had healed tear of hymen, followed by 8 (8.6%) having bruise over vagina. An overall positivity was recorded as 21 (22.59%) for sexual assault in serological assessment. Conclusion: The results of the study conclude that about ¼ of each case reported is positive as per semen analysis in female sexual cases. Most of the cases presented were in early adulthood, were reported after 72 hours of the assault and in most cases assailant was known to the victim. Keywords: Assault; Sexual Examination; Injuries; Semen analysis.